Research progress and applications of epigenetic biomarkers in cancer - Gao, Jianjun; Shi, Wujiang; Wang, Jiangang; Guan, Canghai; Dong, Qingfu; Sheng, Jialin; Zou, Xinlei; Xu, Zhaoqiang; Ge, Yifei; Yang, Chengru; Li, Jiehan; Bao, Haolin; et al. (Frontiers in Pharmacology, 2024)
Epigenetic changes are heritable changes in gene expression without changes in the nucleotide sequence of genes. Epigenetic changes play an important role in the development of cancer and in the process of malignancy metastasis. Previous studies have shown that abnormal epigenetic changes can be used as biomarkers for disease status and disease prediction. The reversibility and controllability of epigenetic modification changes also provide new strategies for early disease prevention and treatment. In addition, corresponding drug development has also reached the clinical stage. In this paper, we will discuss the recent progress and application status of tumor epigenetic biomarkers from three perspectives: DNA methylation, noncoding RNA, and histone modification, in order to provide new opportunities for additional tumor research and applications.